2017
DOI: 10.1038/s41598-017-13288-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Studies of a Multidomain Alginate Lyase from Persicobacter sp. CCB-QB2

Abstract: AlyQ from Persicobacter sp. CCB-QB2 is an alginate lyase with three domains — a carbohydrate-binding domain modestly resembling family 16 carbohydrate-binding module (CBM16), a family 32 CBM (CBM32) domain, and an alginate lyase domain belonging to polysaccharide lyase family 7 (PL7). Although AlyQ can also act on polyguluronate (poly-G) and polymannuronate (poly-M), it is most active on alginate. Studies with truncated AlyQ showed that the CBM32 domain did not contribute to enhancing AlyQ’s activity under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The presence of CBM32 domain in AlyQ from Persicobacter sp. CCB-QB2 also did not significantly increase its activity [17]. In this study, we observed that the specific enzymatic activities of TM1 (CBM32-PL7) and TM2 (CBM9-PL7) were 4.6-fold and 6.6-fold higher than that of TM3 (the PL7 catalytic module only), respectively.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The presence of CBM32 domain in AlyQ from Persicobacter sp. CCB-QB2 also did not significantly increase its activity [17]. In this study, we observed that the specific enzymatic activities of TM1 (CBM32-PL7) and TM2 (CBM9-PL7) were 4.6-fold and 6.6-fold higher than that of TM3 (the PL7 catalytic module only), respectively.…”
Section: Discussionmentioning
confidence: 59%
“…Several thousand alginate lyases have been classified into the PL5, 6,7,14,15,17,18,32,34, 36 and 39 families in the CAZy database (http://www.cazy.org/) [4,12]. Some alginate lyases are known to contain one or more carbohydrate-binding modules (CBMs); CBM13, CBM16, and CBM32 are the most common [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A1 (PDB code 2CWS; Yamasaki, Ogura, Hashimoto, Mikami, & Murata, ), AlyQ from Persicobacter sp. CCB‐QB2 (PDB code 5XNR; Sim, Furusawa, & Teh, ), and FlAlyA from Flavobacterium sp. UMI‐01 (PDB code 5Y33; Qin et al., )—hold the β‐jelly roll fold.…”
Section: Production Of Aosmentioning
confidence: 99%
“…This type of architecture is common for many PL family enzymes, but it is less common for alginate lyases, although, in some, but not all enzymes belonging to the PL7 family, accessory modules belonging to CBM13, CBM16 and CBM32 have been identified (24)(25)(26). Currently, the precise roles of these domains in alginate lyases are poorly understood with only weak binding of the CBM32 domains to the oligosaccharide being reported (25,27).…”
Section: Analysis Of the Alginate Binding Properties Of The Non-catalmentioning
confidence: 99%